M MUSEUM SEBAGAI LEMBAGA EDUKASI DALAM RANGKA PRESERVASI BUDAYA:STUDI KASUS MUSEUM GEDONG KIRTYA, BULELENG, BALI : PRESERVASI BUDAYA - Desak Nyoman Tri Widiani Desak (ACARYA PUSTAKA, 2025)
The aims of this research are (1) to find out the background to the Gedong Kirtya Museum holding the Museum Joint Learning Program, (2) to find out how the Joint Learning Program is implemented at the Gedong Kirtya Museum. In this research, researchers used descriptive research with a qualitative approach, data collection was carried out by collecting data through observation, interviews and document study. The results of the research show that the Learning Together with the Museum Program aims to make the government's program a success and introduce this very valuable cultural heritage to the younger generation and the implementation of the Learning Together with the Museum Program has been carried out well by the Gedong Kirtya Museum, the museum has also held competitions or outreach activities regarding the existence and collection of the Gedong Kirtya Museum which involves educational institutions. Therefore, indirectly the Gedong Kirtya Museum has introduced cultural heritage that is worth preserving. Keywords: Museum, Preservation, Local Culture